Honoring Professor Mária Kurdi - Szélpál, Lívia (Hungarian Journal of English and American Studies, 2021)
Book review: Csikai, Zsuzsa, and Rouse, Andrew C., eds. Critical Essays in Honour of Mária Kurdi. Tanulmányok Kurdi Mária tiszteletére. Martonfa: SPECHEL e-editions, 2017. 243 pages. ISBN 978-963-12-9291-6. E-book. 747 HUF.